Dynamic event-triggered L∞ control for switched affine systems with sampled-data switching. (February 2021) - Li, Zhuoyu; Ma, Dan; Zhao, Jun
Abstract: This paper investigates the dynamic event-triggered L ∞ control for switched affine systems under limited communication resources. For switched affine systems, affine terms bring the difficulty on the exclusion of triggering Zeno behavior. The proposed dynamic event-triggered mechanism can preclude the occurrence of triggering Zeno behavior even if affine terms and the exogenous disturbance coexist. Moreover, it further reduces the transmission frequency compared with the static version. The switching chattering phenomenon is avoided by the designed sampled-data switching rule. The co-design method of dynamic event-triggered scheme, switching controller and sampled-data switching rule is provided to achieve practical stability and the L ∞ performance with respect to the external interference. Tools and techniques of time-dependent Lyapunov function are used to obtain sufficient conditions in terms of linear matrix inequalities. Finally, the effectiveness of the developed results is illustrated by an example.